Snakin-2 interacts with cytosolic glyceraldehyde-3-phosphate dehydrogenase 1 to inhibit sprout growth in potato tubers. Issue 1 (19th January 2022) - Li, Liqin; Lyu, Chengcheng; Chen, Jing; Lu, Yifei; Yang, Shiming; Ni, Su; Zheng, Shunlin; Yu, Liping; Wang, Xiyao; Wang, Qiang; Lu, Liming
Abstract : 1. StSN2 and StGAPC1 expression level decreased more in sprouting than dormancy both on transcription and protein process. The coexpression of StSN2 and StGAPC1 in bud eyes and apical buds was verified by immunofluorescence of paraffin sections. 2. StSN2 interaction with StGAPC1 was confirmed by in vivo and in vitro experiments. Overexpression of StGAPC1 depressed sprout growth, similar to StSN2 function. 3. StSN2 interaction with StGAPC1 increased StGAPC1 activity and decreased its oxidative modification to inhibit sprout growth. Abstract: The potato tuber is the main nutrient supply and reproductive organ; however, tuber sprouting can reduce its commercial value. Snakin-2 (StSN2) was first reported as an antimicrobial peptide that positively regulates potato disease resistance. Our recent study suggested StSN2 overexpression inhibited sprout growth, while the sprouting process was accelerated in StSN2 RNAi lines. Cytoplasmic glyceraldehyde-3-phosphate dehydrogenase 1 (StGAPC1) was identified as a candidate protein that interacts with StSN2 in co-immunoprecipitation/mass spectrometry experiments. Here, we report that the expression levels of StSN2 and StGAPC1 decreased during sprouting compared with dormancy. Coexpression of StSN2 and StGAPC1 in bud eyes and apical buds was verified by immunofluorescence analysis of paraffin sections. In addition, interaction of StSN2 and StGAPC1 was confirmed by yeast two-hybrid, co-immunoprecipitation, and split luciferase complementation assays. Overexpression of StGAPC1 depressed sprout growth, which is similar to the function of StSN2, and StSN2 - and StGAPC1 -overexpressing lines showed decreased glucose, fructose, and galactose contents. The interaction of StSN2 and StGAPC1 enhanced StGAPC1 activity and decreased its oxidative modification to inhibit sprout growth. Our results suggest that StSN2 plays a regulatory role in tuber sprout growth through interaction with StGAPC1.